Clinical characteristics and outcome of H1N1 (2009) pneumonia with special reference to radiological features in a tertiary care hospital in northern Karnataka - Jyothi Karanji; Gajanan S. Gaude (Al Ameen Medical College, 2013)
Background: In late March 2009, an outbreak of respiratory illness, later proved to be caused by swine origin influenza A (H1N1) virus (S-OIV) was identified in Mexico. Thereafter many countries worldwide have reported the incidence of this pneumonia. The present study was undertaken to evaluate the clinical characteristics and radiological features of positive cases of confirmed Influenza A H1N1 (2009) infection in a tertiary care hospital in northern part of Karnataka. Material and Methods: A retrospective analysis of medical charts, laboratory investigations and radiographs of 57 positive cases of Influenza A H1N1 (2009) infection was done. Throat swab of all these patients were confirmed by real time RT- PCR assay (reverse transcriptase polymerase chain reaction method). Results: A total of 57 cases were infected with influenza A H1N1 (2009) virus. They belonged to 20 to 40 years of age, with the mean age being 35. Acute onset cough, fever and breathlessness were the most common clinical presentation. Some of them had chest pain, sore throat, rhinitis, hemoptysis and vomiting. Twenty patients had co-morbid conditions like type 2 diabetes mellitus, IHD and one of them was a case of carcinoma breast on chemotherapy. Features of leucopenia, leucocytosis, thrombocytopenia, raised liver function parameters and raised blood serum creatinine were the major laboratory features. Radiologically, almost all of the patients had confluent ground glass appearance on chest radiographs, with bilateral distribution of the patchy infiltrations in multiple lung zones. A typical consolidation was conspicuous by its absence. Pleural effusion was present in 14% of the cases. A total of 35 patients required mechanical ventilation and 26 of them succumbed to death. Hypoxemia and thrombocytopenia were the major risk factors for the mortality with H1N1 pneumonia. It was also observed that involvement of four or more lung zones and bilateral peripheral opacities was associated with higher mortality in these patients. Raised liver function test parameters and raised serum creatinine levels were the indicators for development of MODS. Mortality on mechanical ventilator for these patients was very high (p<0.0008). Conclusions: The present study revealed the serious nature of H1N1 pneumonia with high mortality due to ARDS and MODS in patients requiring mechanical ventilation. This emphasizes the need for early institution of the antiviral therapy and close monitoring in these patients.